1971
DOI: 10.4141/cjps71-050
|View full text |Cite
|
Sign up to set email alerts
|

Polara, a Low Coumarin Cultivar of Sweetclover

Abstract: not available

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Therefore, the success of forage cultivar development based on any of the Melilotus species will depend on a combination of increasing dry matter production and decreasing coumarin content. A number of cultivars of Melilotus have been released to date; Acuma, Cumino, Denta, Polara (Smith and Gorz, 1965 ; Goplen, 1971 ) for M. albus and Norgold (Goplen, 1981 ), N28, N29 (Gorz et al, 1992 ) for M. officinalis . The Melilotus breeding program at Lanzhou University is specifically focused on the development of new cultivars with adaptation to the vast temperate grazing environments of China (Luo et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the success of forage cultivar development based on any of the Melilotus species will depend on a combination of increasing dry matter production and decreasing coumarin content. A number of cultivars of Melilotus have been released to date; Acuma, Cumino, Denta, Polara (Smith and Gorz, 1965 ; Goplen, 1971 ) for M. albus and Norgold (Goplen, 1981 ), N28, N29 (Gorz et al, 1992 ) for M. officinalis . The Melilotus breeding program at Lanzhou University is specifically focused on the development of new cultivars with adaptation to the vast temperate grazing environments of China (Luo et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Caspar et al (1982) demonstrated that dicumarol levels in excess of 20 ppm were required to generate a toxic response in calves, with levels of 60 ppm causing death. "Low-coumarin" cultivara of sweetclover have been developed (Goplen, 1971(Goplen, , 1981; however, because this characteristic is recessive, outcrossing of the low-coumarin cultivare with high-coumarin wild Melilotus is an unavoidable problem (Goplen and Weber, 1966). Goplen et al (1964) determined that spoiled low-coumarin cultivare contaminated with up to 10% of high-coumarin plants could safely be fed to cattle.…”
Section: Introductionmentioning
confidence: 99%
“…The development of new Melilotus cultivars with low Cou content will be significant to the forage industry. A range of cultivars or breeding lines of Melilotus have been released to date, such as Norgold, N28, and N29 (Goplen, 1981;Gorz et al, 1992) for M. officinalis and Acuma, Cumino, Polara, and Denta (Smith and Gorz, 1965;Goplen, 1971) for M. albus.…”
mentioning
confidence: 99%